Udział kobiet w afgańskim życiu politycznym w teorii i praktyce – wstęp do analizy - Krzyżanowski, Marcin (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
Presented article is an attempt to describe the multidisciplinary phenomenon of participation of Afghan women in national policy-making process. Due to the low volume of this publication Author focused on presenting an overall view of the subject and discussing only the most important factors determining the dynamics of its changes. The first part of the article describes in general terms the Afghan cultural and political context, to the extent necessary for the proper presentation of the topic for those, who are not familiar with the realities of the country. In the second part Author discusses the most important laws setting out a framework for the participation of women in country’s political life. Part three describes the practical manifestations of women’s involvement in politics, with particular emphasis on issues related to the election processes. The last part is an attempt to forecast subject’s future developments
Keywords: polityka; równość płci; kobiety; patriarchalizm; Afganki; gender; dyskryminacja; Afganistan; wybory